The squeaky door - MacDonald, Margaret Read, 1940- (HarperCollinsPublishers, 2006)
When Little Boy is frightened by a squeaky bedroom door, his grandmother brings in various animals to help him feel secure enough to sleep. Includes notes on the story's origins.